THE RELATIONSHIP BETWEEN LINGUISTIC INTELLIGENCE AND STUDENTS’ COGNITIVE ABILITIES IN THE SUB-CONCEPTS OF DISASTER RESPONSE ACTIONS - Rifqy Kiara Cahyaningrum; Partaya Partaya; Aditya Marianti (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2022)
This research is a correlational study that develops quantitative descriptive research. This study aims to obtain information about the relationship between linguistic intelligence and cognitive abilities in the sub-concepts of disaster response actions and other factors that influence it besides linguistic intelligence. This research was conducted in September 2019. The population of this study was MTS Darul Irfan students of Serang City in the academic year 2019/2020. The sampling technique uses simple random sampling. The sample was 24 students of class VII-A. The data collection method is done by tests, documentation, student worksheets, and observations. Based on the regression and linearity test results, it can be concluded that the simple regression analysis with the equation Y=37.986+0.038X is linear. Based on the result of quantitative research, the correlation coefficient between linguistic intelligence and cognitive abilities is 0,0030. This correlation coefficient value indicates that H0is rejected and H1is accepted, meaning linguistic intelligence weakens student cognitive abilities. In this study, other factors affect student cognitive abilities, among others, strategies and learning methods, development of learning media in schools, and environmental factor of students.